Jenis Pengemasan dan Penyimpanan terhadap Kualitas Cabai Rawit (Capsicum frutescens L.) (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2023)
Chili is a horticultural commodity that is easily damaged physically, chemically and biologically. This study aims to determine the effect of the type of packaging, storage and interaction on the quality of cayenne pepper (Capsicum frutescens L.). This research will be carried out at the Horticulture Laboratory, Seed Science and Technology Laboratory and Plant Breeding Laboratory, Faculty of Agriculture, Syiah Kuala University, Banda Aceh City. The research was carried out from March 2022 to May 2022. This research was carried out using a Completely Randomized Block Design (RCBD) with a factorial pattern of 6 x 2 with 3 replications so that there were 12 treatment combinations and 36 experimental units. Each experimental unit consisted of 50 samples of cayenne pepper, so that in total there were 1,800 cayenne peppers. The parameters observed included measurement of weight loss, color measurement, organoleptic test, measurement of water content, measurement of capsaicin levels and vitamin C levels. The best quality of cayenne pepper was found in the type of banana leaf packaging. The best quality of cayenne pepper was found at low temperature storage. The best quality of cayenne pepper was found in the combination of banana leaf packaging and storage at low temperatures.
Keywords: Cayenne pepper; packaging; quality; storage